Effect Analysis of Unbalanced Electric Load in Ship at Three Phase Synchronous Generator on Laboratory Scale - Radhin Dzaky Yulisetiawan; Eddy S. Koenhardono; Sardono Sarwito (Jurnal Teknik ITS, 2016)
The generator is the main power supply of electricity in the ship. The generator can supply each ship’s electricity consumer regarding the generator capacity and consumer requirement. Until now, some research been developed to increase the efficiency of the generator. Besides that, in the operation of generator, there are several problems that cause the generator works inefficient, which one is an unbalanced load on each phase in generator. This final project analyzed the effect of unbalanced load in three phase synchronous generator. In this research conducted a simulation of the operational of the generator on board ship with a laboratory experiment. This research includes the phasor diagram drawing, efficiency, as well as vibrations generated by the generator at several loading conditions. The research results were when the generator on 50% load of the generator capacity (240 Watt), and the loads are getting unbalanced, the power produced by the generator is increased 30%, and the neutral current value also increased by 50%, compared with balanced load condition. Besides that, the vibration value in each condition is tend to fluctuate. This is applied for another experiment. In accordance to the generator operation on ship is when the loads are getting unbalance, the fuel consumption also increase. This shows that there is dissipation use in fuel oil consumption